2019
DOI: 10.1016/j.isci.2019.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Charge Characteristics of Agouti-Related Protein Implicate Potent Involvement of Heparan Sulfate Proteoglycans in Metabolic Function

Abstract: SummaryThe endogenous melanocortin peptide agouti-related protein (AgRP) plays a well-known role in foraging, but its contribution to metabolic regulation is less understood. Mature AgRP(83-132) has distinct residues for melanocortin receptor binding and heparan sulfate interactions. Here, we show that AgRP increases ad libitum feeding and operant responding for food in mice, decreases oxygen consumption, and lowers body temperature and activity, indicating lower energy expenditure. AgRP increased the respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…It has been previously observed that AgrP interacts with heparan sulfate, a linear polysaccharide found on cell surfaces and extracellular matrices. 30 The binding of AgrP with heparan sulfate is of significant interest due to its potential implications in various physiological processes. Additionally, minerals such as Ca, Fe, and Zn known to modulate protein interactions and play essential roles in cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously observed that AgrP interacts with heparan sulfate, a linear polysaccharide found on cell surfaces and extracellular matrices. 30 The binding of AgrP with heparan sulfate is of significant interest due to its potential implications in various physiological processes. Additionally, minerals such as Ca, Fe, and Zn known to modulate protein interactions and play essential roles in cellular functions.…”
Section: Discussionmentioning
confidence: 99%